MODEL KELAS MULTIDIMENSIONAL: INOVASI PEMBELAJARAN ABAD 21 UNTUK MENINGKATKAN HASIL BELAJAR SISWA PELAJARAN ILMU PENGETAHUAN ALAM - Fairus Qamila (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
MULTIDIMENSIONAL CLASS MODELS: INNOVATION LESSONS IN THE 21ST CENTURY TO IMPROVE SCIENCE LEARNING OUTCOMES AbstractThe 21st century learning is an effort to facilitate students in the 21st century to get the best learning experience so they can achieve learning goals effectively. This research is aimed to recognize the enhancement of science student learning achivement with implementation of multidimensional classroom model. This research used a classroom action research from Kemmis and MC Taggart. The sample of 28 students. The research was done in three cycle. The percentage achivement every cycle was increased. By looking at the result obtained in each cycle, it can be concluded that there was enhancement of science student learning achivement with implementation of multidimensional classroom model. AbstrakPembelajaran abad 21 merupakan upaya memfasilitasi peserta didik di abad 21 untuk mengalami pengalaman belajar terbaik sehingga dapat mencapai tujuan pembelajaran secara efektif. Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa pada pelajaran IPA dengan menerapkan model kelas multidimensional. Penelitian ini merupakan jenis Penelitian Tindakan Kelas (PTK) model Kemmis dan MC. Taggart. Sampel penelitian berjumlah 28 siswa. Penelitian ini dilakukan sebanyak 3 siklus. Persentase ketuntasan pada setiap siklus terus meningkat. Hasil penelitian menunjukan terdapat peningkatan hasil belajar siswa pada pelajaran IPA dengan menerapkan Model kelas Multidimensional.